Ztráta zraku a predsudky - Cálek, O (Casopis lekaru ceskych, 1990)
Major or complete loss of eyesight is a serious interference with the activity and life of the affected subject. It is generally assumed that these subjects are quite helpless and that they suffer general deterioration. This is at variance with results of training and rehabilitation during which many thus affected subjects become independent, which is essential for their social integration. Despite this they have to experience sociopsychological attitudes which are prejudices with a typical stereotype which ignore the unique structure of everybody's potential who lost eyesight. The source of prejudices is general lack of information of people as regards actual sequelae of loss of eyesight and the emotional reaction of people with normal eyesight. A certain part is also played by tradition which does not take into account results of modern care of thus affected subjects. Prejudices cause in subjects with severely affected eyesight and in blind persons mental stress and render their actual social integration (employment, partnership etc.) more difficult. The solution is to train resistance against prejudices in thus affected subjects and to intensify health education on the given problem.
Keywords: lidé; postoj; slepota; předsudek; Attitude; Blindness; Prejudice; Humans